Search strategies formulation among library and information science students in online database - Othman, Roslina; Junurham, Nur Leyni Nilam Putri (International Digital Organization for Scientific Information, 2014)
The purpose of this study is to investigate the search strategies practiced by postgraduate students at Department of Library and Information Science in IIUM. As became future librarians or information professionals in organization of library or reputable institutions, the good search strategies is very important in order to satisfy and guide users in locate the information through various sources especially electronic sources such as online database. The findings of this study would contribute to understand of LIS students search strategies on the use of online database in order to develop better formulation of queries as well as to increase the confident in use online database when retrieve the information with an effective ways. Besides that, since LIS students get proper training and education pertaining to search skills in courses offers, the advent of technology have change their roles as a facilitator in retrieve the information and play roles in assisting and facilitating normal users from other faculties and fields to find information in efficient ways. Furthermore, the focus of this study is to examine the reasons causing the failure in getting the needed results by the postgraduate students at Department of Library and Information Science in IIUM. In addition, the study included the minor findings of which are the most online database that they always use and the purpose of use online database. Average time of searching information also taken into account in order to understand their expertise and knowledge skills in general. The study employed the descriptive survey research and utilized selfadministrative questionnaire for data collections. Data collected of the study presented in table of frequency and percentage followed by brief description of the findings.